ANALISIS PENDAPATAN USAHATANI BAWANG MERAH DI DESA MOPUSI KECAMATAN LOLAYAN KABUPATEN BOLAANG MONGONDOW - Mangkat, Rama Rizki; Dumais, Joachim N.K.; Katiandagho, Theodora Maulina (Sam Ratulangi University, 2022)
The objective of this research is to anaylyze the income of red onion farming in Mopusi Village Lolayan Sub District of Bolaang Mongondow Regency. The Research started in November 2020 until January 2021. The primary data for this study was collected from direct interview with the red onion farmers using quistioner. The secondary data was obtained from Village Ofice of Mopusi and also from the internet. The Sampling was made with Census because there are only two red onion farmers. The research result showed that the red onion farming is profitable for the farmer because the income as per hectare that was received by the farmers in Mopusi Village Lolayan District as big as Rp. 195.265.361 in one growing season with R/C ratio 3,06.